Effects of high-frequency prefrontal rTMS on heart frequency rates and blood pressure in schizophrenia - Campana, Mattia; Wagner, Elias Maximilian; Wobrock, Thomas; Langguth, Berthold; Landgrebe, Michael; Eichhammer, Peter; Frank, Elmar; Cordes, Joachim; Wölwer, Wolfgang; Winterer, Georg; Gaebel, Wolfgang; Hajak, Göran; et al. (Journal of psychiatric research, 2021)
Background - Repetitive transcranial magnetic stimulation (rTMS) is a safe non-invasive neuromodulation technique used for the treatment of various neuropsychiatric disorders. The effect of rTMS applied to the cortex on autonomic functions has not been studied in detail in patient cohorts, yet patients who receive rTMS may have disease-associated impairments in the autonomic system and may receive medication that may pronounce autonomic dysfunctions. - Methods - Using data from the ‘rTMS for the Treatment of Negative Symptoms in Schizophrenia’ (RESIS) trial we evaluated the effect of rTMS applied to the left dorsolateral prefrontal cortex (DLPFC) on autonomic nervous system-related parameters such as blood pressure (BP) and heart rate (HR) in both reclining and standing postures from screening up to 105 days after intervention among patients with schizophrenia. - Results - 157 patients received either active (n = 76) or sham (n = 81) rTMS treatment. Apart from gender no significant group differences were observed. During intervention, Linear Mixed Model (LMM) analyses showed no significant time × group interactions nor time effects for any of the variables (all p > 0.055). During the whole trial beside a significant time × group interaction for diastolic BP (p = 0.017) in the standing posture, no significant time × group interactions for other variables (all p > 0.140) were found. - Conclusion - These secondary analyses of the largest available rTMS trial on the treatment of negative symptoms in schizophrenia did not show a significant effect of active rTMS compared to sham rTMS on heart rate or blood pressure, neither during the intervention period nor during the follow-up period.